Business Incubators In The Entrepreneurship Ecosystem In Indonesia Mediated By Government Support And Intellectual Capital - Novita Susiang, Maria Imelda (Commercium : Journal of Business and Management, 2024)
This research looks at the dynamic interplay in Indonesia's entrepreneurial ecosystem between government funding, intellectual capital, and the success of business incubators. Using quantitative methods, we surveyed 150 business owners involved with several incubators, investigating the intricacies of government programmes, intellectual capital dynamics, and the perceived effectiveness of these incubators. Structural Equation Modelling with Partial Least Squares (SEM-PLS) was used to examine the survey data, uncovering complex correlations and explaining the mediating role of intellectual capital. Our findings have practical consequences for policy makers, incubator managers, and entrepreneurs aiming for sustainable firm growth. These findings also provide additional insights to the theoretical framework that directs entrepreneurship research in the implications of these results.